Diagnosis and Treatment of VOD/SOS After Allogeneic Hematopoietic Stem Cell Transplantation - Bonifazi, Francesca; Barbato, Francesco; Ravaioli, Federico; Sessa, Mariarosaria; Defrancesco, Irene; Arpinati, Mario; Cavo, Michele; Colecchia, Antonio (Frontiers in Immunology, 2020)
Hepatic veno-occlusive disease (VOD) or sinusoidal obstruction syndrome (SOS) is a rare complication characterized by hepatomegaly, right-upper quadrant pain, jaundice and ascites, occurring after high dose chemotherapy, hematopoietic stem cell transplantation (HSCT) and, less commonly, other conditions. Here we review pathogenesis, clinical appearance and diagnostic criteria, risk factors, prophylaxis and treatment of the VOD occurring post-HSCT. The injury of the sinusoidal endothelial cells with loss of wall integrity and sinusoidal obstruction is the basis of development of post-sinusoidal portal hypertension responsible of clinical syndrome. Risk factors associated with the onset of VOD and diagnostic tools have been recently updated both in pediatric and adult setting and here are reported. Treatment includes supportive care, intensive management and specific drug therapy with defibrotide. Because of its severity, particularly in VOD with associated multi-organ disease, prophylaxis approaches are under investigation. During the last years, decreased mortality associated to VOD/SOS has been reported being it attributable to a better intensive and multidisciplinary approach.